The moon race popularization through the pages of National Geographic - Pereira, Luís (2021)
The National Geographic Society (1888) emerged as a small scientific society designed to encourage and spread geographic knowledge to be nowadays one of the largest scientific and educational organizations in the world. The National Geographic Magazine evolved from an intermittent periodical, written in academic language and without illustrations, into an easily read and attractively illustrated albeit factually accurate monthly magazine. In the aerospace field, the Society sponsored the balloon Explorer II expedition (1935) whose crew observed the Earth’s curvature for the first time. In the post-war period the exploration of the atmosphere upper layers continued with V-2 missile tests and the first space photographs obtained were published (1950). After the creation of NASA (1958), the Society stood out due to its privileged coverage of the Mercury, Gemini and Apollo programs. The National Geographic flag would accompany the Apollo 11 crew. Space exploration opened a new frontier for National Geographic readers and the magazine circulation increased from 2.2 to 5.6 million subscribers, between 1957 and 1967. We will present an analysis of the articles published within the scope of the Moon race in terms of their content and impact on the collective perception of events that are amongst the most outstanding of the twentieth century